Sustainable Conservation Through the Interrelations Between Rural Architecture and Life: The Case of Çomakdağ - Kurtulus, Vacide Betul; Guchan, Neriman Sahin; Şahin Güçhan, Neriman (Emerald Group Publishing Ltd, 2025)
PurposeThe paper aims to propose a new approach to the sustainable conservation of rural heritage with the aim of understanding the relations between built environment and society. In the document "Concerning Rural Landscapes as Heritage" by ICOMOS-IFLA, it is argued that there is an interaction between daily life practices and the physical environment for production and cultural activities (ICOMOS, 2017). The main objective of the study is to underline the importance and necessity for this interaction continue for the sustainable conservation of rural areas.Design/methodology/approachThis paper investigates the relationship between the built environment and daily practices in Turkey's & Ccedil;omakdag Region, known for its significant rural architecture and enduring traditions. Through on-site investigation, the study explores the evolution of these relationships across various scales, including buildings, settlements and the region itself. This multi-scale approach aims to identify remaining cultural values and user needs.FindingsTraditional ways of life have undergone a transformation, impacting the interactions between inhabitants and their natural, agricultural and architectural spaces. The primary drivers of these changes are shifts in income sources, technological advancements and infrastructural developments within the settlements. While maintaining a connection between the built environment and daily life practices remains essential, contemporary living conditions and altered routines present challenges to this continuity.Originality/valueThis study builds on previous research on the & Ccedil;omakdag Region. Batur (2010) explored the region's architectural features, including colors and ornamentation. Kurtulus and G & uuml;& ccedil;han (2020) focused on Kizilaga & ccedil; village, examining typical house characteristics. This research offers a new perspective on rural heritage preservation. It emphasizes the importance of maintaining the interrelationship between daily life and the built environment across various scales for sustainable conservation.
Keywords: Rural Heritage Conservation; Sustainable Conservation; Comakdag; Rural Life; Rural Architecture